Epidemiological evidence for work load as a risk factor for osteoarthritis of the hip: a systematic review. - Sandra I Sulsky; Laura Carlton; Frank Bochmann; Rolf Ellegast; Ulrich Glitsch; Bernd Hartmann; Dirk Pallapies; D Seidel; Yi Sun (PLoS ONE, 2012)
Objective Osteoarthritis of the hip (OA) is a common degenerative disorder of the joint cartilage that presents a major public health problem worldwide. While intrinsic risk factors (e.g, body mass and morphology) have been identified, external risk factors are not well understood. In this systematic review, the evidence for workload as a risk factor for hip OA is summarized and used to derive recommendations for prevention and further research. Methods Epidemiological studies on workload or occupation and osteoarthritis of the hip were identified through database and bibliography searches. Using pre-defined quality criteria, 30 studies were selected for critical evaluation; six of these provided quantitative exposure data. Results Study results were too heterogeneous to develop pooled risk estimates by specific work activities. The weight of evidence favors a graded association between long-term exposure to heavy lifting and risk of hip OA. Long-term exposure to standing at work might also increase the risk of hip OA. Conclusions It is not possible to estimate a quantitative dose-response relationship between workload and hip OA using existing data, but there is enough evidence available to identify job-related heavy lifting and standing as hazards, and thus to begin developing recommendations for preventing hip OA by limiting the amount and duration of these activities. Future research to identify specific risk factors for work-related hip OA should focus on implementing rigorous study methods with quantitative exposure measures and objective diagnostic criteria.